ASPEK PERTIMBANGAN DALAM SIMULASI FERMENTASI FASE GAS BERBASIS CFD - Triwibowo, Bayu (Universitas Negeri Semarang, 2013)
In the midst of restrictions issue on the use of fossil fuels, the world began to move towards the use of renewable fuels. One such fuel is hydrogen. Hydrogen itself could synthesized from fermentation method. Complex phenomenon will be difficult to be analyzed simultaneously and comprehensively when using conventional techniques. Optimation would be important since yield hydrogen from fermentation method was very small. Cause of few obstacles such as comprehensive phenomenon data not exsted mades this process very difficult to optimize. Simulation of hydrogen fermentation based on CFD would be one of the solution to retrieve phenomenon data comprehensively